A Comparative Discourse Analysis of Spanish Past Narrations From the ACTFL OPI and OPIc. (30th October 2017) - Brown, Alan V.; Cox, Troy L.; Thompson, Gregory L.
Abstract: The ACTFL Oral Proficiency Interview (OPI) and accompanying proficiency guidelines have become a mainstay in academic foreign language assessment. In 2006, an asynchronous electronic interface of the OPI was made available in which candidates are asked to record themselves responding to questions delivered aurally via computer, labeled the Oral Proficiency Interview‐computer (OPIc). Thompson, Cox, and Knapp (2016 ) found that both instruments produced similar results but that many students in their sample who scored at the Advanced Low level on the traditional OPI scored one sublevel higher on the OPIc. The primary objective of the present study is to analyze lexical features, i.e., lexical diversity and lexical density, and discursive features, i.e., temporal and repair fluency, of students' speech from a subset of OPI and OPIc exams to examine the relationship between the language elicited from each exam type, i.e., face‐to‐face and via computer. The research consists of two studies that focus on candidates who received (1) an Advanced Mid rating on both assessments, and (2) those who received Advanced Mid on the OPIc and Advanced Low on the OPI. While the two exams did not seem to elicit disparate levels of lexical density and diversity, significant differences surfaced in measures of fluency.